Effects of priming and storage on seed quality of Adan rice - Samuel, Henrita (2020)
Adan rice is a traditional rice planted by the indigenous people in Borneo, especially Bario, Ba’kelalan. Long Semadoh (Malaysia) and Krayan, Indonesia. It is a very important crop among the indigenous people as a source of economic income and recently as agritourism product. However, the production of Adan rice is low due to the limited technology and knowledge applied in the agronomic practices particularly in the quality of planting materials used. Therefore, this study aims to determine the priming methods in enhancement of seed quality and seed storage that can increase the production and yield. Adan rice has fine seed with small size, low surface area (27.04±1.10 mm²) and aspect ratio (24.83%). The seed of Adan rice was of high quality with high purity (99.77%), favorable moisture content (10.54%) and high germination rate (91.3%). Hydropriming in 35°C within 12 hours and thermopriming 45°C in 12 hours was optimal for Adan rice seeds. Ambient temperature storage has a significantly higher in germination rate (95%) compared to 86% and 79% as for refrigerator and freezer, respectively. Seed enhancement using hydropriming and keeping them in ambient temperature are recommended for short period seed storage. However, improvement in storage method for Adan rice should be further studied for a longer storage period.